69Effect of smoking on treatment outcomes among newly diagnosed Tuberculosis patients in Shimla city India. (2nd September 2021) - Gupta, Anmol; Kumar, Vineet
Abstract: Background: World health organization in 2015 had adopted "End TB Strategy" aimed at ending the global TB epidemic by 2035. Tobacco smoking has been reported to be associated with many aspects of TB disease, including increased vulnerability to being infected, recurrence with TB and related mortality. Methods: A prospective cohort study was carried out among newly diagnosed tuberculosis patients of Shimla city which is the capital of Himachal Pradesh, a northern state of India. Data related to smoking status was collected using the standard questionnaire which was used for collection of data regarding tobacco use in Global Adult Tobacco Survey (GATS). Details of the participant's final treatment outcomes after end of standardized treatment of 6 months was collected from the treatment records of the patients. Results: 72 TB patients were included as study subjects. The prevalence of smoking came out to be 37.5%. In our analyses, the risk of unfavorable treatment outcomes was higher among smokers (p value 0.049), Smokeless tobacco users (p value 0.031) and those with history of harmful alcohol use (p value 0.002). Conclusions: There is high prevalence of smoking among TB patients and risk factors associated with unfavorable treatment outcome are smoking, Smokeless tobacco and history of harmful alcohol use. Key messages: Smoking and smokeless tobacco cessation programmes need to be targeted at Tuberculosis patients. Tuberculosis patients with alcohol related problems should be identified at the time of diagnosis and should be attached with de-addiction centre